Community Education for a Dignified Last Phase of Life for Migrants: A Community Engagement, Mixed Methods Study among Moroccan, Surinamese and Turkish Migrants - de Voogd, Xanthe (Int J Environ Res Public Health, 2020)
Community engagement and -education are proposed to foster equity in access to care and to ensure dignity of migrant patients in the last phase of life, but evidence is lacking. We evaluated nine community educational interactive meetings about palliative care (136 participants totally)- co-created with educators from our target groups of Moroccan, Surinamese and Turkish migrants—with a mixed methods approach, including 114 questionnaires, nine observations, nine interviews with educators, and 18 pre- and post- group- and individual interviews with participants. Descriptive and thematic analysis was used. 88% of the participants experienced the meetings as good or excellent. Educators bridged an initial resistance toward talking about this sensitive topic with vivid real-life situations. The added value of the educational meetings were: (1) increased knowledge and awareness about palliative care and its services (2) increased comprehensiveness of participant’s wishes and needs regarding dignity in the last phase; (3) sharing experiences for relief and becoming aware of real-life situations. Community engagement and -education about palliative care for migrants effectively increases knowledge about palliative care and is a first step towards improved access to palliative care services, capacity building and a dignified last phase of life among migrants.